THE WEINSTEIN EFFECTS: FORECASTING THE GENESIS OF CANCEL CULTURE IN HOLLYWOOD INDUSTRY - Alexei Wahyudiputra; Abdika Taslih Amrullah; Diaz Adrian (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
The phenomenon of cancel culture has become a common, even effective, way of convicting people who are deemed to be a deviant of social norms. The practice of cancel culture is massively emerging on mainstream lens by the stimulation of Harvey Weinstein’s cases in Hollywood discourse, or known as the Weinstein Effects. The article aims to examine cancel culture in Hollywood and the relation between this phenomenon with Weinstein Effects, and point out a hysteresis in Hollywood celebrity culture due to this event. The research is conducted qualitatively by synthesizing information from various journal articles and online news regarding celebrity discourse. Furthermore, the basis of analytical discussion within this article is Foucauldian premise regarding genealogy and Bourdieusian postulation on cultural hysteresis.